A routing strategy for spatial networks based on harmonic centrality - Lin, Hong; Xia, Yongxiang; Li, Xingyi; Gao, Xiaoxu (Frontiers in Physics, 2023)
With the rapid development of networks, the traffic in the networks has increased sharply, resulting in frequent congestion. Especially in spatial networks, such as railway network, aviation network and sensor network, congestion not only affects the user's experience, but also causes serious economic losses. Therefore, in this paper, we effectively identify the high-load nodes in the spatial networks by considering harmony centrality and degree. On this basis, we design HD routing strategy by avoiding these key nodes, which can enhance the traffic throughput of spatial networks efficiently. The results provide new idea and direction for the design of routing strategies for spatial networks.